STRATEGI KYAI DALAM MENINGKATKAN MUTU DAN DAYA SAING PONDOK PESANTREN: Studi Kasus di Ponpes Roudhotul Mustofa dan Ponpes Arrosyidiyah Rejotangan Tulungagung - Suprihno; Rohmawati, Eti (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2023)
This research wants to reveal the strategies of Islamic boarding school kyai in improving the quality and competitiveness of their educational institutions at Roudhotul Musthofa Rejotangan Islamic Boarding School and Arrosidiyah Rejotangan Islamic Boarding School, Tulungagung Regency. Results of qualitative descriptive research located at Roudhotul Mustofa Islamic Boarding School and Arrosidiyah Islamic Boarding School for 4 months, namely June - September 2023. Primary data sources are Kyai, Ustadz and Islamic boarding school students. Meanwhile, the secondary data is the researcher's observations with documents and field studies which are supporting research materials. Data analysis techniques include data collection, condensation and presentation of data and drawing conclusions. The results of this research show that the Kyai's strategy in improving quality and competitiveness is working well, characterized by formulation, implementation and evaluation, making Islamic boarding schools develop rapidly. The formulation includes a vision and mission and analyzes strengths and weaknesses. Implementing the strategy by implementing superior programs, namely tahfidz Qur'an and khatam kitab kuning within a certain time and forming an Islamic boarding school work team. evaluate with external environmental assessments, organizational assessments and performance assessments.